How do civil servants view the importance of collaboration and scientific knowledge for climate change adaptation?. Issue 1 (2nd January 2016) - Temby, O.; Sandall, J.; Cooksey, R.; Hickey, G.M.
Abstract : Successfully navigating the complex challenges posed by wicked environmental problems requires that inter- and intra-organisational policy networks share information, integrate knowledge and collaborate in decision-making processes. However, within government, the hierarchical and mechanistic design of bureaucratic agencies is often not well suited to this task. As a result, governments have increasingly implemented mechanisms encouraging interagency collaboration to better address complex environmental governance challenges, an example being climate change adaptation. In this article, we take an 'inside look' at how civil servants, working in the government agencies responsible for progressing climate change adaptation strategies, view collaboration and draw on science-based knowledge to inform decision-making. Focusing on civil servants in agencies from the states of Victoria, Australia, and New York, the USA, and the province of British Columbia, Canada, the results show variation across jurisdictions in terms of the collaborative mechanisms used. However, respondents in all three jurisdictions reported remarkably consistent views on the importance of collaboration and scientific knowledge to their role. Overall, our results suggest a gap exists between the motivation of civil servants to collaborate and draw on scientific information and their capacity/ability to do so, pointing to potential institutional and systemic barriers that require further research.